Low-Cyclic Loading Tests of Self-Centering Variable Friction (SCVF) Brace. (17th November 2020) - He, Qingguang; Bai, Yanxia; Wu, Weike; Du, Yongfeng
Abstract : A novel assembled self-centering variable friction (SCVF) brace is proposed which is composed of an energy dissipation system, a self-centering system, and a set of force transmission devices. The hysteretic characteristics and energy dissipation of the SCVF brace with various parameters from low-cyclic loading tests are presented. A finite element model was constructed and tested under simulated examination for comparative analysis. The results indicate that the brace shows an atypical flag-type hysteresis curve. The SCVF brace showed its stable self-centering ability and dissipation energy capacity within the permitted axial deformation under different spring and friction plates. A larger deflection of the friction plate will make the variable friction of this SCVF brace more obvious. A higher friction coefficient will make the energy dissipation capacity of the SCVF brace stronger, but the actual friction coefficient will be lower than the design value after repeated cycles. The results of the fatigue tests showed that the energy dissipation system formed by the ceramic fiber friction blocks and the friction steel plates in the SCVF brace has a certain stability. The finite element simulation results are essentially consistent with the obtained test results, which is conducive to the use of finite element software for calculation and structural analysis in actual engineering design.